Lattice strain and tilt mapping in stressed Ge microstructures using X‐ray Laue micro‐diffraction and rainbow filtering. Issue 5 (4th August 2016) - Tardif, Samuel; Gassenq, Alban; Guilloy, Kevin; Pauc, Nicolas; Osvaldo Dias, Guilherme; Hartmann, Jean-Michel; Widiez, Julie; Zabel, Thomas; Marin, Esteban; Sigg, Hans; Faist, Jérôme; Chelnokov, Alexei; et al.
Abstract : The lattice tilts and full strain tensor are measured in Ge micro‐devices under uniaxial or biaxial stress using standard and rainbow‐filtered Laue micro‐diffraction. Maps with sub‐micrometre resolution of the strain tensor components are in very good agreement with finite element simulations. Abstract : Laue micro‐diffraction and simultaneous rainbow‐filtered micro‐diffraction were used to measure accurately the full strain tensor and the lattice orientation distribution at the sub‐micrometre scale in highly strained, suspended Ge micro‐devices. A numerical approach to obtain the full strain tensor from the deviatoric strain measurement alone is also demonstrated and used for faster full strain mapping. The measurements were performed in a series of micro‐devices under either uniaxial or biaxial stress and an excellent agreement with numerical simulations was found. This shows the superior potential of Laue micro‐diffraction for the investigation of highly strained micro‐devices.